Structural and ferroelectric properties of epitaxial BaZrxTi1-xO3 thin films - Engelhardt, Stefan; Mietschke, M.; Molin, Christian; Gebhardt, S.; Faehler, S.; Nielsch, Kornelius; Huehne, R. (Journal of Physics D: Applied Physics, 2016)
Epitaxial BaZrxTi1-xO3 (BZTO) thin films with Zr contents of x = 0, x = 0.12 and x = 0.2 were grown by pulsed laser deposition on (0 0 1)-oriented single crystalline SrTiO3 substrates utilizing an additional conducting SrRuO3 buffer layer. It was found that the oxygen pressure during the deposition Po2 heavily influences the lattice constants and the microstructure of BZTO. A low Po2 of 0.01 mbar gives rise to a significant tetragonal distortion. Texture measurements reveal that an undisturbed epitaxial growth is only achieved for BZTO films prepared in 0.01 mbar oxygen. In contrast, the formation of twins was observed for higher Po2. A detailed microstructural analysis indicates that the sample preparation in low Po2 prevents a preferential growth of columnar grains within the BZTO layers and leads to smoother film surfaces. BZTO thin films deposited with optimized deposition parameters show characteristic ferroelectric polarization behavior. The saturation polarization at room temperature declines with increasing Zr content and the characteristic ferroelectric hysteresis diminishes. Temperature-depended measurements of the relative permittivity reveal the existence of a broad transition range and a significant shift of the phase transition temperature to lower values for increasing Zr content.
CRIS-Team Scopus Importer:2023-03-20
Keywords: BaTiO; epitaxial thin films; ferroelectric materials; pulsed laser deposition